Hubungan Pengetahuan Ibu Dengan Pemberian Imunisasi Dasar Di Wilayah Kerja Puskesmas Sopobutar Kabupaten Dairi - Parida Hanum; Lasria Simamora; Henny Rista (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: The percentage of children aged 0 to 11 months who received complete basic immunization reached 75.5% of the target of 92.9%, with a performance achievement of 75.34%. Complete Basic Immunization Coverage (IDL) in North Sumatra Province in 2019 was 85.17%. For data on Complete Basic Immunization (IDL) coverage in Dairi district, there is 82.02%, this figure shows that Dairi district has not yet achieved the strategic plan that has been determined. This study aims to analyze the relationship between maternal knowledge and the provision of basic immunizations in the working area of the Sopobutar health center, Dairi Regency in 2022. Method: This type of research is analytical with a cross-sectional design. The research was conducted in the working area of the Sopobutar Community Health Center, Dairi Regency, North Sumatra Province. The research was conducted from May to June 2022. The population in the study were all mothers who had 1 year old babies recorded in the working area of the Sopobutar Community Health Center, 38 people and using total sampling techniques. Data analysis in this research includes Univariate Analysis and Bivariate Analysis with the chi square test, using a significance level of 5% (p value <0.05). Results: The results showed that the majority of mothers' knowledge was sufficient, 22 people (57.9%) and the majority of babies received complete basic immunization, 26 people (68.4%). The statistical test results show a p value of 0.002 <0.05, meaning there is a significant relationship between knowledge and providing basic immunization to babies in the Sopobutar Community Health Center Working Area. Conclusion: P value = 0.002 <0.05, which means Ha is accepted and Ho is rejected, which means there is a significant relationship between knowledge and providing basic immunizations to babies in the Sopobutar Community Health Center Working Area in 2022. It is hoped that mothers who have babies will increase their insight and concern regarding basic immunization for babies, regarding immunization programs according to schedule and providing complete immunizations.